ANALYSIS OF CREDIT SYSTEM REFORM IN HIGHER EDUCATIONAL INSTITUTIONS - Khamrayev Nodir Zokir ugli (European Science Publishing, 2025)
Credit system is a teaching management system. It uses the lowest total credits required as a measure of the amount of student learning and graduation criteria, and uses students’ self course selection as the premise. It overcomes the drawbacks of the existing academic system. It truly enables students learn to use, and play to their strengths. It helps to improve the quality of education, promote the education reform, and improve the speed and quality of our personnel training.
Keywords: Credit system, teaching management system, self course selection, quality education.